Thé development of the grammatical competence through direct corrective feedback among tenth year students at unidad educativa josé ángel palacio of the city of loja during the 2016 – 2017 school year - Gaona Abad, Leodan Francisco (2018)
The aim of this research work was to develop grammatical competence through direct corrective feedback among tenth year students at Unidad Educativa José Ángel Palacio of the city of Loja during the 2016-2017 school year. The scientific, descriptive, analytical- synthetic and the statistical method were used to analyze, the information obtained. In addition, tests and questionnaires were applied to 25 students to diagnose the students’ English level and to get students’ reactions in front of direct corrective feedback. Also, observation sheets and a diary were used to collect information about students’ performance in each lesson. The results indicated that the students improved satisfactory in English constructing sentences, using the appropriate form of the verbs and to make and answer questions. In conclusion the application of direct corrective feedback as a complementary resource was acceptable. Students applied grammatical pattens in a better way in all the duties delevop in the intervention plan.